Mineral dust aerosol distributions, its direct and semi-direct effects over South Africa based on regional climate model simulation. (March 2015) - Tesfaye, M.; Tsidu, G. Mengistu; Botai, J.; Sivakumar, V.; deW. Rautenbach, C.J.
Abstract: The present contribution investigates the seasonal mean mass distributions, direct and semi-direct climatic effects of desert dust aerosols over South Africa, using the 12 year runs of Regional Climate Model (RegCM4). The results have shown that the desert dust particles which burden the western and southern regions of South Africa are mainly produced from the Kalahari and Namib Desert areas. At the surface and within the atmosphere, the short- and long-wave radiative forcing (RF) of dust showed contrasting effects. However, due to the dust short-wave RF dominant influence, the Net-RF of dust causes reduction on net radiation absorbed by the surface via enhancing radiative heating in the atmosphere. The radiative feedbacks of desert dust particles predominantly result in a positive response on net atmospheric radiative heating rate, Cloud Cover (CC) and cloud liquid water path. The CC enhancement and Net-RF of dust, cooperatively, induce reduction in surface temperature (up to −1.1 K) and surface sensible heat flux (up to −24 W/m 2 ). The presence of desert dust aerosol also causes boundary layer height reduction, surface pressure enhancement and dynamical changes. Overall, the present contribution underscores the importance of including the effects of wind-eroded dust particles in climate change studies over South Africa. Highlights: Desert dust aerosols in South Africa have positive feedback on low-level cloud cover. Desert dust aerosols in South Africa have negative feedback on ST, SSHF and PBL. Dust induced ΔCC has important role in governing other climatic effects of dust. Climate change studies in South Africa need to include wind-eroded dust particles.